Evaluating abundance of deciduous trees in production forests along small stream - Åström, Jessica (2020)
Riparian zones are important for many ecological functions such as for providing shade to streams and leaf litter to instream organisms, as well as acting as filters for sediments and excess nutrients that are released during forestry operations. Riparian areas are also important for preservation of biodiversity. Over time, forestry policies in Sweden have changed and this has had effects on the management of forests. For example, in 2013 the Strategic Management Objectives (SMO) were introduced, aiming to act as a guideline for an expected level of environmental consideration. Within the SMOs, there is a goal to preserve and manage functional riparian buffer zones adjacent to streams. One way of reaching this goal is to encourage deciduous tree species in the riparian zones at all stages of forestry operations. The aim with this thesis was to investigate how forestry policy actions have changed management of riparian zones and if historic forest management has impacted how we can meet the SMOs today. The main focus was to understand if deciduous tree species already exist within the riparian zones of small streams or if there is a need for changed or intensified management to encourage deciduous trees. My study was performed in Vindeln, Västerbotten County, northern Sweden. I measured stand characteristics of 16 riparian buffer zones of four different age classes, i.e., <1975, <1993, <2013 and <2019. Each of the age classes has been subject to different forest policies and thus different management within buffers. I found that the 1993 Forestry Act has had a positive effect on deciduous cover in riparian buffers of small streams. On the contrary, the introduction of SMOs in 2013 has not yet improved the buffer management, at least with regard to deciduous tree species and some riparian functions, i.e. dead wood provision and shading. A reoccurring pattern in my results was that there is a time lag from the time the buffer is created until the riparian buffer is functioning as intended. It seems that the most recently created buffers have not yet had time to recover from historical management. If the goal of the SMOs is to have ecologically functioning buffers and stable conditions, e.g. canopy cover adjacent to streams, there is likely a need to change the forestry practices in riparian zones. For example, leaving wider buffers and potentially selectively logging coniferous trees within those buffer strips can encourage deciduous tree species and compensate for economic losses.